Olfactory Senses Modulate Food Consumption and Physiology in Drosophila melanogaster - He, Jianzheng; Tuo, Wenjuan; Zhang, Xueyan; Dai, Yuting; Fang, Ming; Zhou, Ting; Xiu, Minghui; Liu, Yongqi (Frontiers in Behavioral Neuroscience, 2022)
Both sensory and metabolic processes guide food intake. Olfactory inputs help coordinate food appreciation and selection, but their role in food consumption and post-feeding physiology remain poorly understood. In this study, using Drosophila melanogaster as a model system, we investigated the effects of olfactory sensory neurons (OSNs) on food consumption, metabolism and stress responses. We found that dysfunction of OSNs affects diverse processes, including decreased food consumption, increased triacylglycerol level, enhanced stress resistance to starvation or desiccation, and decreased cold resistance. Decreased neuropetide F receptor (NPFR) level or increased insulin activity in OSNs inhibited food consumption, while impaired NPF signaling or insulin signaling in OSNs increased resistance to starvation and desiccation. These studies provide insights into the function of the olfactory system in control of feeding behaviors and physiology.